An Analysis Of The Determinants Of Unemployment Among The Educated Population In The Sulampua Region: A Provincial Panel Data Approach For 2015–2024 - Indah Christiani; Mohamad Ichwan Tandju (Cakrawala Repositori IMWI)
This research aims to analyze the determinants of educated unemployment in the Sulawesi, Maluku, and Papua (Sulampua) regions during the period 2015–2024. Educated unemployment is one of the strategic issues in regional economic development because it reflects an imbalance between improving the quality of human resources and the ability of the economy to create job opportunities that are in accordance with the level of education of the workforce. This study uses a quantitative approach with panel data regression combining time and regional dimensions. The variables include the number of industries, GRDP growth, per capita expenditure, average years of schooling, labor force participation, wages, unemployment, minimum wage, and inflation. Model selection using the Chow, Hausman, and Lagrange Multiplier tests indicates that the Fixed Effect Model (FEM) is the most appropriate. The results of the estimates show that the open unemployment rate and the provincial minimum wage have a positive and significant influence on educated unemployment, while the variables of the number of industries, GDP growth rate, per capita expenditure, average length of schooling, labor force participation rate, average hourly wage, and inflation do not show a significant influence. These findings indicate that the dynamics of educated unemployment in the Sulampua region are more influenced by labor market conditions in aggregate than by economic growth indicators alone, so that more inclusive economic development policies are needed, strengthening industrial structures that are able to absorb educated workers, and increasing the compatibility between the education system and labor market needs.